ಕನ್ನಡ ಮಧ್ಯಮ ಪ್ರಯೋಗಶಾಲಾ ಪಠ್ಯ - (:unkn) unknown (My University, 2019)
This volume is a compilation prepared keeping in view the varied genres of Kannada language and culture. The audio-visual lessons in this volume are designed in such a way to help the Kannada L2 learners to develop their listening, speaking, reading and writing skills.
Kannada Intermediate Course Language Laboratory
Keywords: Kannada